Các hợp chất tritecpen glycosit khung cucurbitane phân lập từ quả mướp đắng (Momordica charantia L.) (Phần 1) - Yến, Phạm Hải; Anh Tuấn, Hoàng Lê; Dung, Dương Thị; Minh, Châu Văn; Nhiệm, Nguyễn Xuân; Thúy Hằng, Đan Thị; Hải Yến, Dương Thị; Cúc, Nguyễn Thị; Thanh, Bùi Văn; Kiệm, Phan Văn (Vietnam Journal of Chemistry, 2014)
From the methanol extract of fruits of Momordica charantia L., five compounds: goyaglysoside-c (1), goyaglysoside-d (2), momordicoside F1 (3), momordicoside N (4), and momordicoside M (5) were isolated. Their structures were determined by spectrometry methods and in comparison with the published data. Keywords: Momordica charantia L., goyaglysoside-c, goyaglysoside-d, momordicoside F1, momordicoside N, and momordicoside M.